Challenges and Opportunities Shaping Smallholders’ Engagement with Formal and Informal Markets for Food and Livelihood Security: A Rift Valley, Kenya Case Study Analysis - Longfield, Lynsey (Université d'Ottawa / University of Ottawa, 2014)
This case study analysis looks at four communities in Rift Valley, Kenya including Matisi, Moi’s Bridge, Sirende and Waitaluk. The research focuses on the role of markets in achieving food and livelihood security for the smallholders in these communities and smallholders’ perceptions of the roles of the Government of Kenya and other institutions in facilitating market access. The largest challenges to market participation, as reported by the smallholders in the studied communities, include low yields, weather inconsistencies, and lack of land. In terms of the Government of Kenya, many smallholders noted the benefits of participating in groups as they are subsequently offered training or field days and subsidies. A significant group of respondents did comment on their lack of interest in joining similar groups as they were seen as unstable or corrupt. The potential roles of formal and informal markets to increase food security were also analyzed. All smallholders wished to be participating in informal markets, but twenty-five percent were constrained by the lack of surplus produce. Similarly, although many reported their desire to be participants in formal markets lack of surplus produce, price fluctuations, inconsistent weather patterns, transportation costs and post- harvest losses or food waster were recognized as significant barriers. In order to mitigate these constraints, most smallholders recommended subsidies on inputs and the overall restructuring of markets. It is recommended that organizations and governments implement a livelihood diversification policy program or initiative to diversify and intensify agricultural activities and other non-agricultural activities. This case study analysis demonstrates the need to recognize the importance of local contexts, specifically Rift Valley as much of the research done in Kenya is found in Nairobi and surrounding areas and cautions labeling communities as food secure based on favorable conditions.
Keywords: Food security; Informal; Formal; Markets; Livelihood diversification